Prognosis after acute exacerbation in patients with interstitial lung disease other than idiopathic pulmonary fibrosis. (10th December 2020) - Miyashita, Koichi; Kono, Masato; Saito, Go; Koyanagi, Yu; Tsutsumi, Akari; Kobayashi, Takeshi; Miki, Yoshihiro; Hashimoto, Dai; Nakamura, Yutaro; Suda, Takafumi; Nakamura, Hidenori
Abstract: Background: Acute exacerbation (AE) is recognized as a life‐threatening condition with acute respiratory worsening in idiopathic pulmonary fibrosis (IPF). AE also occurs in fibrotic interstitial lung disease (ILD) other than IPF, including other types of idiopathic interstitial pneumonias (IIPs), ILD associated with collagen vascular disease (CVD–ILD), and chronic hypersensitivity pneumonia (CHP). However, the clinical impact after AE in those patients is still unclear. Methods: A retrospective review of 174 consecutive first‐episodes with AE of ILD in our institution from 2002 to 2016 was performed. AE was defined according to the revised definition and diagnostic criteria proposed by an international working group in 2016. Clinical characteristics, 90‐day survival, and the requirement of long‐term oxygen therapy (LTOT) after AE were evaluated in each underlying ILD. Results: There were 102 patients with AE of IPF (AE–IPF) and 72 with AE of ILD other than IPF, including non‐IPF IIPs (n = 29) and secondary ILD (n = 43) [CVD–ILD (n = 39), CHP (n = 4)]. In CVD–ILD, rheumatoid arthritis (n = 17) was most common. The 90‐day mortality after AE was 57% in IPF, 29% in non‐IPF IIPs, and 33% in secondary ILD. After AE, ILD other than IPF had a significantly better survival rate than IPF ( P < 0.001). Among survivors, the rates of patients requiring LTOT after AE were 63% in IPF, 35% in non‐IPF IIPs, and 46% in secondary ILD, respectively. Conclusions: AE of ILD other than IPF might have a better prognosis than AE–IPF, but both are fatal conditions that cause chronic respiratory failure.